A SUGGESTED MODEL FOR TEACHING EXPOSITORY TEXT COMPREHENSION FOR EFL UNIVERSITY STUDENTS - Novalita Fransisca Tungka (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
Reading course in university level is supposedly designed to promote EFL students’ reading comprehension skills and strategies, in order to assist them in comprehending information as delivered by reading text. However, it is considered that EFL students often face have difficulties in comprehending English text, specifically English expository text. Therefore, appropriate model for teaching expository text comprehension for the students who experience difficulties in comprehending expository text is highly needed. Appropriate comprehension instructions, such as questioning and analyzing text structure, should become the focus of teaching reading to students to achieve this main goal of reading course objective. If these instructions are combined with video, under the framework of experiential learning theory, students will have rich experiences in promoting their reading comprehension skills and strategies. This article discusses the possibility of integrating video in reading course and proposes the possible activities of integrating video with reading comprehension activities.